The Estimated Impact of Human Papillomavirus Vaccine Coverage on the Lifetime Cervical Cancer Burden Among Girls Currently Aged 12 Years and Younger in the United States - Chesson, Harrell W. (Sex Transm Dis, 2014)
Using a previously published dynamic model, we illustrate the potential benefits of human papillomavirus vaccination among girls currently 12 years or younger in the United States. Increasing vaccine coverage of young girls to 80% would avert 53,300 lifetime cervical cancer cases versus 30% coverage and 28,800 cases versus 50% coverage.